GAMBARAN PENGETAHUAN IBU POST PARTUM TENTANG PERAWATAN PERINEUM DI RUANGAN POST NATAL CARE DI RSUD. LABUANG BAJI MAKASSAR TAHUN 2020 - Sartika Sartika (Jurnal Ilmiah Hospitality, 2021)
Perineal rupture occurs in almost every first delivery and it is highly possible to occur in the next delivery. In the 2020, there were 2.7 million cases of perineal rupture injuries worldwide, with 26% of them followed by slow recovery, which takes more than 7 days after childbirth. Perineal rupture is also a significant issue in Asian. In Indonesia, one in five delivery ended with the death of mother because of perineal rupture which cause bleeding and infection. This research attempted to assess the knowledge of postpartum mothers regarding perineal care in the Post Natal Care of Labuang Baji Hospital, Makassar. Descriptive observational employed in carrying out the research. 30 women who were undergoing postpartum treatment were used as population for this research, where sampling technique used was total sampling. Data collected through through questionnaires. The research revealed that out of 30 respondents studied, 5 (16.7%) have good knowledge, 20 (66.7%) have enough (fair) knowledge, and 5 (16.7%) have poor knowledge. As a conclusion, the majority of postpartum mothers in the Post Natal Care ward of RSUD Labuang Baji Makassar have fair knowledge. The research recommend that the medical staffs-specially those who are working at Post Natal Care-to continuously provide education to postpartum mothers about proper perineal care